The Effect of University Autonomy on Training and Scientific Research: A Case Study at Vietnam National University of Agriculture - Uoc, Nguyen Cong; Huy, Nguyen Duc (VNU Journal of Science: Education Research; Vol 35 No 4DO - 10.25073/2588-1159/vnuer.4306, 2019)
As an attribute of the university, autonomy for universities in Vietnam has been an inevitable, increasingly strong trend in recent years. This paper presents a study of university autonomy policies in Vietnam and the impact of university autonomy on training results and scientific research at Vietnam National University of Agriculture for the period 2015-2018.